2023
DOI: 10.3389/fpsyt.2022.1049432
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric traits and intracerebral hemorrhage: A Mendelian randomization study

Abstract: BackgroundPsychiatric traits have been associated with intracerebral hemorrhage (ICH) in observational studies, although their causal relationships remain uncertain. We used Mendelian randomization analyses to infer causality between psychiatric traits and ICH.MethodsWe collected data from genome-wide association studies of ICH (n = 361,194) and eight psychiatric traits among Europeans, including mood swings (n = 451,619), major depressive disorder (n = 480,359), attention-deficit/hyperactivity disorder (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Previous evidence for intracerebral hemorrhage is also limited. One MR study has suggested a lack of association between schizophrenia and intracerebral hemorrhage, 42 and another study found little association between second‐generation antipsychotic drugs and intracerebral hemorrhage among patients with schizophrenia. 36 If there exists an explanation in favor of our finding, it may be the more common use of anticoagulant drugs due to cardiac problems (eg, atrial fibrillation) among patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence for intracerebral hemorrhage is also limited. One MR study has suggested a lack of association between schizophrenia and intracerebral hemorrhage, 42 and another study found little association between second‐generation antipsychotic drugs and intracerebral hemorrhage among patients with schizophrenia. 36 If there exists an explanation in favor of our finding, it may be the more common use of anticoagulant drugs due to cardiac problems (eg, atrial fibrillation) among patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we used a more stringent threshold of p < 5E-08 when examining the three pairwise associations between MDD and CSVD clinical phenotypes. Furthermore, a recent MR in 2023 examined the risk association between MDD and ICH and found no causal relationship (Wang et al, 2022). Because we used larger and more comprehensive GWAS datasets for both MDD and CSVD clinical phenotypes, our findings may provide more reliable evidence of an association between the two.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, positive psychological health could reduce the incidence of stroke (Lambiase et al., 2015 ). A recent MR analysis demonstrated that genetically determined mood swings were causally related to the risk of intracerebral hemorrhage (ICH) (Wang et al., 2022 ). IA and aSAH share up to 50% genetic characteristics with ICH (Bakker et al., 2020 ; Mayerhofer et al., 2022 ; Tromp et al., 2014 ; Wahab et al., 2019 ; Yamada et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%